2019
DOI: 10.1038/s41393-019-0318-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived injustice after spinal cord injury: evidence for a distinct psychological construct

Abstract: Study design Cross-sectional study.Objective To identify unique predictors of perceived injustice compared with depression symptoms within the first year after SCI. Setting Inpatient rehabilitation program in a large urban region in the Southwestern United States. Methods A sample of 74 participants with median time since injury of 52 days completed measures of perceived injustice, depression symptoms, posttraumatic stress symptoms, expected disability, pain intensity, and anger. Results Three unique predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…All measures were meaningfully correlated when compared to the IEQ overall score, as well as with both subscales independently. Furthermore, as is consistent with prior research, the IEQ overall score was associated with measures of anger (ρ = .384), pain (ρ = .444), depression (ρ = .370), anxiety (ρ = .342), fatigue (ρ = .430), disability (ρ = .379), and HRQOL including Mental HRQOL (ρ = .556) and Physical HRQOL (ρ = .584; Monden et al, 2019; Sullivan et al, 2008; Trost et al, 2015).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…All measures were meaningfully correlated when compared to the IEQ overall score, as well as with both subscales independently. Furthermore, as is consistent with prior research, the IEQ overall score was associated with measures of anger (ρ = .384), pain (ρ = .444), depression (ρ = .370), anxiety (ρ = .342), fatigue (ρ = .430), disability (ρ = .379), and HRQOL including Mental HRQOL (ρ = .556) and Physical HRQOL (ρ = .584; Monden et al, 2019; Sullivan et al, 2008; Trost et al, 2015).…”
Section: Resultssupporting
confidence: 86%
“…The findings from the correlation analysis are notable and consistent with our hypothesis and previous research involving those individuals with spinal cord injury (Monden et al, 2019); traumatic injury (Trost et al, 2015); and fibromyalgia (Rodero et al, 2012). The IEQ factor of Severity/Irreparability of loss appears to be more strongly correlated with physical manifestations of MS, and therefore it can be interpreted that individuals may perceive physical symptoms of MS as severe, permanent, and not recoverable.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Few studies have examined the impact of perceived injustice on outcomes following SCI (Monden et al, 2019; Trost, Monden, Buelow, Boals, & Scott, 2016; Trost et al, 2017). Consistent with the literature, Trost et al (2017) found that among adult inpatients admitted for SCI rehabilitation, higher perceived injustice was associated with depression and posttraumatic stress symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Stigma is significantly related to several of the psychosocial outcomes; however, these bivariate relationships do not account for other important factors (covariates) that may also contribute to the outcome. For example, many studies show pain intensity predicts greater depression symptoms and injustice appraisals among individuals with SCI (Bombardier et al, 2016; Cairns et al, 1996; Monden et al, 2019). Also, following SCI, being male and having decreased mobility are both predictors of lower life satisfaction (Dijkers, 1999; Putzke et al, 2002).…”
Section: Discussionmentioning
confidence: 99%